11β‐Hydroxysteroid dehydrogenase type 1 within muscle protects against the adverse effects of local inflammation. Issue 4 (18th October 2016) - Hardy, Rowan S; Doig, Craig L; Hussain, Zahrah; O'Leary, Mary; Morgan, Stuart A; Pearson, Mark J; Naylor, Amy; Jones, Simon W; Filer, Andrew; Stewart, Paul M; Buckley, Christopher D; Lavery, Gareth G; et al.
Abstract: Muscle wasting is a common feature of inflammatory myopathies. Glucocorticoids (GCs), although effective at suppressing inflammation and inflammatory muscle loss, also cause myopathy with prolonged administration. 11β‐Hydroxysteroid dehydrogenase type 1 (11β‐HSD1) is a bidirectional GC‐activating enzyme that is potently upregulated by inflammation within mesenchymal‐derived tissues. We assessed the regulation of this enzyme with inflammation in muscle, and examined its functional impact on muscle. The expression of 11β‐HSD1 in response to proinflammatory stimuli was determined in a transgenic murine model of chronic inflammation (TNF‐Tg) driven by overexpression of tumour necrosis factor (TNF)‐α within tissues, including muscle. The inflammatory regulation and functional consequences of 11β‐HSD1 expression were examined in primary cultures of human and murine myotubes and human and murine muscle biopsies ex vivo . The contributions of 11β‐HSD1 to muscle inflammation and wasting were assessed in vivo with the TNF‐Tg mouse on an 11β‐HSD1 null background. 11β‐HSD1 was significantly upregulated within the tibialis anterior and quadriceps muscles from TNF‐Tg mice. In human and murine primary myotubes, 11β‐HSD1 expression and activity were significantly increased in response to the proinflammatory cytokine TNF‐α (mRNA, 7.6‐fold, p < 0.005; activity, 4.1‐fold, p < 0.005). Physiologically relevant levels of endogenous GCs activated by 11β‐HSD1 suppressed proinflammatory cytokine output (interkeukin‐6, TNF‐α, and interferon‐γ), but had little impact on markers of muscle wasting in human myotube cultures. TNF‐Tg mice on an 11β‐11β‐HSD1 knockout background developed greater muscle wasting than their TNF‐Tg counterparts (27.4% less; p < 0.005), with smaller compacted muscle fibres and increased proinflammatory gene expression relative to TNF‐Tg mice with normal 11β‐HSD1 activity. This study demonstrates that inflammatory stimuli upregulate 11β‐HSD1 expression and GC activation within muscle. Although concerns have been raised that excess levels of GCs may be detrimental to muscle, in this inflammatory TNF‐α‐driven model, local endogenous GC activation appears to be an important anti‐inflammatory response that protects against inflammatory muscle wasting in vivo . © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.